(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article explores the methods and innovative games used to develop fine motor skills. Particularly, the development of fine motor skills directly influences the formation of intellectual, creative, and linguistic abilities. Pedagogical approaches, the Montessori method, didactic games, and modern technologies are analyzed in terms of their effectiveness in enhancing fine motor development. Additionally, the article examines legal and regulatory documents in the educational system of Uzbekistan and their application in practice.